Исследования Малополовецкого археологического комплекса в 2008 г. - Лысенко, С.Д.; Лысенко, С.С. (Археологічні дослідження в Україні, 2009)
In 2008, Fastiv archaeological expedition studied 10 burials (175—184) of the Bronze Age, Early Iron Age and Ancient Rus time on the territory of 1104 м2 at Malopolovetske 3 burial ground. Burial 181 with 7 pendants of Pidhirtsi type was the most interesting. The joint research at Malopolovetske 2a settlement with geophysicists from the T. Shevchenko Kyiv National University revealed several geomagnetic anomalies. The territory of 12 м2 was excavated including a pit of Bilohrudiv type.